5-alpha-dihydrotestosterone elevations associated with phentermine use. (August 2018) - Pearson, Scott M.; Trujillo, Jennifer M.; McDermott, Michael T.
Background: A case of 5-alpha-dihydrotestosterone (DHT) elevation associated with phentermine initiation is reported, and possible mechanisms are discussed. There are no published reports of this association in the literature. Methods: Clinical and laboratory information is described. Results: A 72-year-old male with metastatic prostate cancer taking dutasteride to lower his DHT levels initiated phentermine 15 mg daily for weight loss. His DHT level drawn within 1 week prior to starting phentermine was 9.9 pg/ml. When reporting for follow up 2 weeks later, his DHT level had increased to 114 pg/ml. The DHT level was checked again 2 weeks after that visit, and had increased to 174 pg/ml. At that time, phentermine was discontinued, and 1 week later, the DHT level had decreased to 20.1 pg/ml. Over the next 4 months, the patient's DHT levels were maintained at less than 20 pg/ml. Phentermine 15 mg daily was then reinitiated while his DHT level was 7.5 pg/ml. Two weeks after resuming phentermine, his DHT level had again increased to 196 pg/ml. The patient's phentermine was then discontinued, and around 1 week later, his DHT level had fallen to 5.1 pg/ml. Conclusion: A 72-year-old male with metastatic prostate cancer experienced profound increases in DHT upon initiation of phentermine despite continuation of his baseline dutasteride therapy. The etiology of these increases is still unclear.